N-[4-(Di-2-pyrrolylmethyl)phenyl]acetamide - SENGE, MATHIAS (My University, 2007)
The crystal structure of the title compound, C17H17N3O, shows the formation of infinite chains of molecules that are linked via hydrogen bonds involving the acetamide group. The carbonyl O atom forms hydrogen bonds with both a pyrrole NH group and another acetamide NH unit. In addition, the carbonyl O atom is involved in a weak intramolecular interaction with the neighboring aryl group, thus connecting different chains.
PUBLISHED
Keywords: Chemistry; crystal structure